Criminal Law Perspective In The General Elections That Occurred In Indonesia - Hidayatulloh, Syarif (Jurnal Justiciabelen, 2023)
The enactment of Law Number 7 of 2017 concerning General Elections is proof that Indonesia really designs elections on a strong, constitutional, legal basis and regulates everything related to elections on a legal basis. Enforcement of election crimes in Indonesia needs to be improved as an effort to create a democratic system that is certain and just. Without legal certainty it will lead to anarchism and result in death, therefore democracy must provide legal certainty to all parties who seek justice. So the supremacy of law must be prioritized in guarding the democratic process in Indonesia. Whether the election criminal law enforcement mechanism is enforced from the start in accordance with the provisions of procedural law (due process of law) or not (undue process), if it has been implemented in accordance with the provisions of procedural law then justice has been carried out and upholds the ideology envisioned by the supremacy of law ( Rechtstaat) is based on democratic ideals to realize comprehensive justice so that election criminal law is used as a tool to postpone the ideological commitment to the ideals of establishing the Indonesian state. The aim of this research is to determine the perspective of criminal law on the implementation of elections in Indonesia. The method used in writing this research is normative juridical using statutory regulations and context.